British crime survey, 2000: teching dataset (Crime Survey for England and Wales, 2003)
The British Crime Survey, 2000 (BCS) Teaching Dataset has been prepared solely for the purpose of teaching and student use. The dataset will help class tutors to incorporate empirical data into their courses and thus to develop student skills in quantitative methods of analysis. Many of the names of the variables and value labels are those used in the original BCS files. However, some variables have been recoded for ease of use and may vary from the original BCS data. The original BCS 2000 dataset is held at the UKDA under SN:4463. (Note that the main British Crime Survey has now become the Crime Survey for England and Wales, but titles of older studies in the series remain the same.)